Answer:
x = -1
y = 2
Explanation:
5x - 6y = -17
-3x - 5y = -7
I will eliminate variable x first:
Multiply the first equation by 3
15x - 18y = -51
Multiply the second equation by 5
-15x - 25y = -35
Now subtract the second equation from the first equation:
15x - 18y = -51
-15x - 25y = -35
0x - 43y = -86
-43y = -86
Divide both sides by -43
Negative + Negative = Positive
y = 2
Now eliminate variable y:
Multiply the first equation by 5
25x - 30y = -85
Multiply the second equation by -6 (Negative switches all of the signs)
18x + 30y = 42
43x + 0y = -43
43x = -43
Divide both sides by 43
x = -1
Check work:
5(-1) - 6(2) = -17
-5 - 12 = -17
-17 = -17
Correct
-3(-1) - 5(2) = -7
3 - 10 = -7
-7 = -7
Correct